Coping with stress and health behaviors in collegiate athletes training in team sports - Łukasz Bojkowski; Kamila Litwic-Kaminska (Physical Education of Students, 2025)
Background and Study Aim. Coping with stress may influence decisions regarding engagement in health-related behaviors. This, in turn, can affect the well-being and overall functioning of students. Therefore, the aim of the present study was to examine the relationships between stress coping styles and health behaviors among collegiate-level male and female athletes training in team sports.